Collagen-chitosan 3-D nano-scaffolds effects on macrophage phagocytosis and pro-inflammatory cytokine release. (3rd July 2016) - Mahmoudzadeh, Aziz; Mohsenifar, Afshin; Rahmani-Cherati, Tavoos
Abstract: Macrophages are effector cells in the innate and adaptive immune systems and in situ exist within three-dimensional (3-D) microenvironments. As there has been an increase in interest in the use of 3-D scaffolds to mimic natural microenvironments in vitro, this study examined the impact on cultured mice peritoneal macrophages using standard 2-D plates as compared to 3-D collagen-chitosan scaffolds. Here, 2-D and 3-D cultured macrophages were evaluated for responses to lipopolysaccharide (LPS), dexamethasone (Dex), BSA (bovine serum albumin), safranal (herbal component isolated from safranal [Saf]) and Alyssum homolocarpum mucilage (A. muc: mixed herbal components). After treatments, cultured macrophages were evaluated for viability, phagocytic activity and release of tumor necrosis factor (TNF)- α and interleukin (IL)-1 β pro-inflammatory cytokines. Comparison of 2-D vs 3-D cultures showed that use of either system – with or without any exogenous agent – had no effect on cell viability. In the case of cell function, macrophages cultured on scaffolds had increases in phagocytic activity relative to that by cells on 2-D plates. In general, the test herbal components Saf and A. muc. had more impact than any of the other exogenous agents on nanoparticle uptake. With respect to production of TNF α and IL-1 β, compared to the 2-D cells, scaffold cells tended to have significantly different levels of production of each cytokine, with the effect varying (higher or lower) depending on the test agent used. However, unlike with particle uptake, here, while Saf and A. muc. led to significantly greater levels of cytokine formation by the 3-D culture cells vs that by the 2-D plate cells, there was no net effect (stimulatory) vs control cultures. These results illustrated that collagen-chitosan scaffolds could provide a suitable 3-D microenvironment for macrophage phagocytosis and could also impact on the formation of pro-inflammatory cytokines.